BRAPCI Explorer: : a new web environment for bibliometric analyzes based on the BRAPCI - Castanha, Rafael Gutierres (2023)
Introduction: In the field of Information Science, the Referential Database of the Database of Journal Articles in Information Science (BRAPCI) is a national reference. However, compared to other databases, BRAPCI provides limited bibliometric metrics. Objective: This search proposes a new web environment called BRAPCI Explorer, focused on bibliometric analyses, by scraping data from the BRAPCI database, enhancing and structuring the visualization of indexed data. Methodology: An R programming language code was developed to perform web scraping on BRAPCI, organizing and structuring the data into an interactive website. This code generates co-authorship networks, author and publication source frequency tables, production graphs by year, and calculates bibliometric indicators, including the number of distinct authors, average documents per author, co-authorship index, total distinct sources, average documents per source, and per year. Results: When testing the new environment, a search with the term ”scientific production“ yielded 1628 distinct documents produced by 2178 distinct authors in 78 distinct publication sources. BRAPCI Explorer was capable of generating the co-authorship network as well as preparing all tables and frequency graphs, in addition to calculating the indicators. Conclusion: It is concluded that BRAPCI Explorer contributes to a better visualization of the data provided by BRAPCI because it presents enhanced visualizations in the form of networks, graphs, and tables, along with bibliometric indicators, all in a single environment.